Spotting the enemy within: Targeted silencing of foreign DNA in mammalian genomes by the Krüppel-associated box zinc finger protein family. Issue 1 (December 2015) - Wolf, Gernot; Greenberg, David; Macfarlan, Todd
Abstract Tandem C2H2-type zinc finger proteins (ZFPs) constitute the largest transcription factor family in animals. Tandem-ZFPs bind DNA in a sequence-specific manner through arrays of multiple zinc finger domains that allow high flexibility and specificity in target recognition. In tetrapods, a large proportion of tandem-ZFPs contain Krüppel-associated-box (KRAB) repression domains, which are able to induce epigenetic silencing through the KAP1 corepressor. The KRAB-ZFP family continuously amplified in tetrapods through segmental gene duplications, often accompanied by deletions, duplications, and mutations of the zinc finger domains. As a result, tetrapod genomes contain unique sets of KRAB-ZFP genes, consisting of ancient and recently evolved family members. Although several hundred human and mouse KRAB-ZFPs have been identified or predicted, the biological functions of most KRAB-ZFP family members have gone unexplored. Furthermore, the evolutionary forces driving the extraordinary KRAB-ZFP expansion and diversification have remained mysterious for decades. In this review, we highlight recent studies that associate KRAB-ZFPs with the repression of parasitic DNA elements in the mammalian germ line and discuss the hypothesis that the KRAB-ZFP family primarily evolved as an adaptive genomic surveillance system against foreign DNA. Finally, we comment on the computational, genetic, and biochemical challenges of studying KRAB-ZFPs and attempt to predict how these challenges may be soon overcome.